Compressive behaviour of unconstrained and constrained integral-skin closed-cell aluminium foam - Duarte, Isabel (2019)
The aim of this paper is to evaluate the quasi-static and dynamic compressive crush performance of integral-skin closed-cell aluminium alloy foam with and without radial constraints. The foam specimens were prepared by the powder compact foaming method. The behaviour under different loading conditions (loading velocity and radial constraints) has been determined by an extensive experimental program. The results show a significant increase in the collapse stress of the integral-skin closed-cell aluminium foam under quasi-static loading when radial constraints are applied. The radial constraint induces a significant strain hardening of the foam, where the densification occurs at lower strains, consequently enhancing the energy absorption per unit volume of the deformed foam. The strain hardening is also sensitive to the foam density, increasing with the density.